Efficient iterative scheme for solving non-linear equations with engineering applications - Shams, Mudassir; Kausar, Nasreen; Agarwal, Praveen; Oros, Georgia Irina (TAYLOR & FRANCIS LTD, 2022)
A family of three-step optimal eighth-order iterative algorithm is developed in this paper in order to find single roots of nonlinear equations using the weight function technique. The newly proposed iterative methods of eight order convergence need three function evaluations and one first derivative evaluation that satisfies the Kung-Traub optimality conjecture in terms of computational cost per iteration (i.e.2(n-1)). Furthermore, using the primary theorem that establishes the convergence order, the theoretical convergence properties of our schemes are thoroughly investigated. On several engineering applications, the performance and efficiency of our optimal iteration algorithms are examined to those of existing competitors. The new iterative schemes are more efficient than the existing methods in the literature, as illustrated by the basins of attraction, dynamical planes, efficiency, log of residual, and numerical test examples.
Keywords: Numerical technique; iterative methods; computational time; optimal order; computational efficiency; ORDER; CONVERGENCE; Engineering; Mathematics